Connecting the dots: Neutrophils at the interface of tissue regeneration and cancer. (October 2021) - Nolan, Emma; Malanchi, Ilaria
Abstract: Knowledge about neutrophil biology has exponentially grown over the past decades. A high volume of investigations focusing on the characterization of their initially unappreciated multifaceted functions have grown in parallel with the immunity and the cancer fields. This has led to a significant gain in knowledge about their functions not only in tissue defence against pathogens and the collateral damage their overactivation can cause, but also their role in tissue repair and regeneration especially in the context of sterile injuries. On the other hand, the cancer field has also intensively focused its attention on neutrophil engagement in the many steps of the tumorigenic process. This review aims to draw the readers' attention to the similar functions described for neutrophils in tissue repair and in cancer. By bridging the two fields, we provide support for the hypothesis that the underlying program driving cancer-dependent exploitation of neutrophils is rooted in their physiologic tissue protection functions. In this view, cross-fertilization between the two fields will expedite the discovery of therapeutic interventions based on neutrophil targeting or their manipulation.